APOE2 Is Associated with Spatial Navigational Strategies and Increased Gray Matter in the Hippocampus - Konishi, Kyoko; Bhat, Venkat; Banner, Harrison; Poirier, Judes; Joober, Ridha; Bohbot, Véronique D. (Frontiers in Human Neuroscience, 2016)
The Apolipoprotein E (APOE) gene has a strong association with Alzheimer’s disease (AD). The ε4 allele is a well-documented genetic risk factor of AD. In contrast, the ε2 allele of the APOE gene is known to be protective against AD. Much of the focus on the APOE gene has been on the ε4 allele in both young and older adults and few studies have looked into the cognitive and brain structure correlates of the ε2 allele, especially in young adults. In the current study, we investigated the relationship between APOE genotype, navigation behavior, and hippocampal grey matter in healthy young adults. 124 healthy young adults were genotyped and tested on the 4on8 virtual maze, a task that allows for the assessment of navigation strategy. The task assesses the spontaneous use of either a hippocampus-dependent spatial strategy or a caudate nucleus-dependent response strategy. Of the 124 participants, 37 underwent structural Magnetic Resonance Imaging. We found that ε2 carriers use a hippocampus-dependent spatial strategy to a greater extent than ε3 homozygous individuals and ε4 carriers. We also found that APOE ε2 allele carriers have more grey matter in the hippocampus compared to ε3 homozygous individuals and ε4 carriers. Our findings suggest that the protective effects of the ε2 allele may, in part, be expressed through increased hippocampus grey matter and increased use of hippocampus-dependent spatial strategies. The current paper demonstrates the relationship between brain structure, navigation behavior, and APOE genotypes in healthy young adults.